2017
DOI: 10.1002/jcp.25778
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of curcumin in inflammatory and immune‐mediated diseases: A nature‐made jack‐of‐all‐trades?

Abstract: Curcumin is a dietary polyphenol from turmeric with numerous pharmacological activities. Novel animal and human studies indicate that curcumin can affect different immune cells, such as various T lymphocyte subsets, macrophages, dendritic cells, B lymphocytes and natural killer cells, which results in decreasing severity of various diseases with immunological etiology. The present review provides a comprehensive overview of the effects of curcumin on different immune cells and immune system-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 227 publications
(125 citation statements)
references
References 181 publications
(280 reference statements)
3
119
2
1
Order By: Relevance
“…24 Curcumin affects many signaling pathways that lead to multiple health benefits. 28 It has been shown to be of benefit in inflammatory conditions [29][30][31][32][33] for the treatment of kidney 34 and liver [35][36][37][38] disorders, metabolic syndromes, 39 diabetes, 40 atherosclerosis, 41,42 dyslipidemia, [43][44][45][46] anxiety and/or depression, 47,48 viral diseases, 49 drug toxicity, 50 musculoskeletal, 51,52 and ischemic injury, 53 as well as having antitumor 49,[54][55][56] and antioxidant actions. 57 Furthermore, curcumin has shown efficacy in the management of degenerative eye conditions.…”
Section: Herbal Medicine Strategymentioning
confidence: 99%
“…24 Curcumin affects many signaling pathways that lead to multiple health benefits. 28 It has been shown to be of benefit in inflammatory conditions [29][30][31][32][33] for the treatment of kidney 34 and liver [35][36][37][38] disorders, metabolic syndromes, 39 diabetes, 40 atherosclerosis, 41,42 dyslipidemia, [43][44][45][46] anxiety and/or depression, 47,48 viral diseases, 49 drug toxicity, 50 musculoskeletal, 51,52 and ischemic injury, 53 as well as having antitumor 49,[54][55][56] and antioxidant actions. 57 Furthermore, curcumin has shown efficacy in the management of degenerative eye conditions.…”
Section: Herbal Medicine Strategymentioning
confidence: 99%
“…It is applied in Ayurvedic medicine for treatment of inflammatory diseases for a long time. This plant and its bioactive polyphenols, curcuminoids, have been shown to exert several therapeutic actions including anti-asthmatic, 34 antioxidant, [181][182][183] immunomodulatory, 35 hepatoprotective, 36,37 antitumor, 38,40,41 and anti-inflammatory 39,184,185 activities.…”
Section: Curcuma Longamentioning
confidence: 99%
“…Curcumin, a highly bioactive herbal component, exhibits antiinflammatory activity through multiple mechanisms including inhibition of the NF-κB pathway. 18 In order to test the therapeutic benefits of curcumin in patients with interstitial cystitis/bladder pain syndrome, we examined the effects of curcumin on CPA-induced cystitis/bladder pain in mice. We found that the oral preadministration of curcumin at 100 mg/kg prevented CPA-induced increases in the…”
Section: Effects Of Curcumin An Inhibitor Of Nf-κbrelated Signalsmentioning
confidence: 99%